The effect of particle initial charge on minimum pickup velocity (Upu) in pneumatic conveying - Zhao, Ya (2022)
Pneumatic conveying experiments involving monodisperse and binary-size mixtures of glass beads with charges in the range of −10 to 10 nC have been carried out. The mass loss method was adopted, with the minimum pickup velocity (Upu) determined as the minimum velocity at which entrainment occurred. Similar to previous studies on minimum fluidization velocity, the Upu increased with particle initial charge for the positively charged particles (0–10 nC). Surprisingly, however, negatively charged particles exhibited an opposite trend such that the Upu decreased with charge magnitude. Therefore, for the particle initial charge range investigated (−10 to 10 nC), Upu increased monotonically with particle initial charge, and the correlations available (Kalman et al., 2005; Tay et al., 2012) mis-predicted Upu by up to 10 % for monodisperse systems and up to 40 % of binary-size systems. This underscores the necessity to account for particle initial charge in such correlations, particularly for polydisperse particle systems.